THE INFLUENCE OF JOB SATISFACTION AND WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES AT THE CUSTOMS AND EXCISE SUPERVISION AND SERVICE OFFICE, TMP BELAWAN - Nadira Salmah; Aminuddin; Nur Augus Fahmi (CV. RADJA PUBLIKA, 2025)
The formulation of the problem in the study is whether the influence of job satisfaction on employee performance, whether the influence of work discipline on employee performance, whether the influence of job satisfaction and work discipline on employee performance at the Customs and Excise Supervision and Service Office TMP Belawan, this study aims to determine and analyze the influence of job satisfaction on employee performance, to determine and analyze the influence of work discipline on employee performance, to determine and analyze the influence of job satisfaction and work discipline on employee performance at the Customs and Excise Supervision and Service Office TMP Belawan. The methods used in this study are validity test, reliability test, classical assumption test, linear regression, and hypothesis test. Data were measured or processed using SPSS, with samples using questionnaires distributed to 72 employees at the Customs and Excise Supervision and Service Office TMP Belawan. The results of this study indicate that the job satisfaction variable has a positive and significant effect on employee performance. The work discipline variable has a positive and significant effect on employee performance. The job satisfaction and work discipline variables have a positive and significant effect on employee performance.